COMPARING EFFECTIVENESS OF TELEREHABILITATION VERSUS INSTITUTION-BASED ADAPTED PHYSICAL ACTIVITY AND THERAPEUTIC EXERCISE PROGRAM ON FATIGUE, PHYSICAL FUNCTIONING, AND EPISODIC DISABILITY FOR CHRONIC FATIGUE SYNDROME IN LONG COVID-19: PROTOCOL FOR A RANDO - Md. Feroz Kabir1, Khin Nyein Yin2*, Mohammad Saffree Jeffree3, Fatimah Binti Ahmedy4, Muhamad Faizal Zainudin5, Ohnmar Htwe6, Sharmila Jahan7, Md. Zahid Hossain8, K M Amran Hossain9, Md. Ahnaf Al Mukit10, Tofajjal Hossain11, Iqbal Kabir Jahid12, Sonjit Ku (Chelonian Research Foundation, 2023)
Background: Adaptive pacing improved fatigue and physical functioning in non-COVID patients with chronic fatigue syndrome. Safe long COVID-19 rehabilitation recommends patient-centred, customised, and safer approaches. There is a research gap on the effectiveness of telerehabilitation versus institution-based Adapted Physical Activity and Therapeutic Exercise Program (APTE) on long COVID-19 patients with chronic fatigue syndrome (CFS). Methods: We planned a three-arm prospective randomised control trial on 124 long COVID-19 cases with chronic fatigue syndrome to determine the effectiveness of APTE in institution-based care versus the telerehabilitation approach compared to active control. Participants will be recruited from a population based on the inception cohort and assigned to three groups with the concealed location process with an enrollment ratio of 1:1:1. Between May and July 2023, Participants will be assessed by blinded assessors and during the baseline evolution posttest. After two months and follow-up after six months post-intervention, the Chalder Fatigue Scale will measure primary outcome fatigue. SF-36 and the DALYs will measure the secondary outcome of physical functioning and episodic disability. Discussion: Previous studies suggest that adapted physical activity effectively manages fatigue symptoms in CFS cases in 12 sessions. In Long COVID-19, chronic fatigue syndrome is a prominent symptom that causes episodic disability and impacts a person's physical functioning, activities, and participation. To manage patients with long COVID-19, Telerehabilitation is a widely accepted process. This study will fill the research gap to determine the appropriate approach to APTE compared to active control. The future direction of the study will guide the determination of interventions in long COVID-19 rehabilitation. Trial registration: The trial is registered prospectively from a primary Clinical Trial Registry side of WHO CTRI/2023/03/050808 [Registered on: 17/03/2023] Keywords: Long COVID, Chronic Fatigue Syndrome, Adapted physical activity and Therapeutic exercise program, Telerehabilitation